Pengawasan Pemerintah Terhadap Pekerja Anak - Andries, Michelle Puteri; Rugebregt, Revency Vania; Nirahua, Garciano (Faculty of Law, Universitas Pattimura, 2024)
Currently in Indonesia child labor is not a new issue because in almost all regions in Indonesia there are still many underage children working. but not in accordance with the regulations that have been made by the government, labor issues and child labor are problems that need serious attention, regulation and supervision from the government. This study aims to analyze the considerations that must be made by the government in overcoming the problem of child labor. The problems studied in this study are about how the form of government supervision of child labor and government supervision procedures for child labor. so that how the function of government supervision of child labor and how the government's responsibility for this and has the aim of examining and analyzing how government policies in protecting child labor are in accordance with the supervisory function, what factors influence the government's responsibility to increase efforts to protect child labor.The method used in analyzing and discussing the problem of Government Supervision of Child Labor is Normative Juridical. This type of research is descriptive-analytical, the sources of legal materials used are primary legal materials and secondary legal materials. research techniques are carried out through literature review followed by descriptive analysis using qualitative methods.The results show that the government has an important responsibility to protect child labor. What the government must consider is ensuring that there is effective supervision to protect child labor. The government also needs to implement clear policies and regulations to protect child labor. This includes developing regulations that provide protection and limit child laborers' access to hazardous industries, as well as providing protection and access to education and health..